IMPLEMENTASI LEMBAGA KEARSIPAN DAERAH DALAM PENGGUNAAN APLIKASI SRIKANDI DI KOTA BENGKULU - Shella Stepani; Novliza Eka Patrisia (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This study aims to analyze the implementation of archives in the use of the SRIKANDI application in Bengkulu City. The research method used is a qualitative method. The results of this study provide a conclusion that the implementation of policies from Donald S. Van Meter and Carl E. Van Horn, it can be concluded that the implementation of the use of the SRIKANDI application in Bengkulu City has not been running optimally. This can be seen from the fact that there are still several OPDs that are not yet active and have not been consistent in using the SRIKANDI application in government administration. In the theory of policy implementation from Donald S. Van Meter and Carl E. Van Horn, it consists of six indicators, namely policy standards and objectives, resources, communication between organizations, organizational characteristics, socio-political and economic environment. Keywords: Archives, SRIKANDI application